2021
DOI: 10.3389/fmicb.2021.744268
|View full text |Cite
|
Sign up to set email alerts
|

The FtcR-Like Protein ActR in Azorhizobium caulinodans ORS571 Is Involved in Bacterial Motility and Symbiosis With the Host Plant

Abstract: Bacterial signal transduction pathways are important for a variety of adaptive responses to environment, such as two-component systems (TCSs). In this paper, we reported the characterization of a transcriptional regulator in Azorhizobium caulinodans ORS571, ActR, with an N-terminal receiver domain and one C-terminal OmpR/PhoB-type DNA binding domain. Sequence analysis showed that ActR shared a high similarity with FtcR regulator of Brucella melitensis 16M known to be involved in flagellar regulation. The struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Previous studies showed that flagellar genes could be activated in response to environmental changes or stress [ 28 , 29 ]. Moreover, comparative sequence analysis in B. melitensis 16M showed that ActR—a protein involved in regulating flagellar and biofilm formation—shared 53.2% genetic similarity with FtcR [ 30 ]. We therefore suspect that FtcR-like regulators could be involved in flagellar biosynthesis and biofilm formation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that flagellar genes could be activated in response to environmental changes or stress [ 28 , 29 ]. Moreover, comparative sequence analysis in B. melitensis 16M showed that ActR—a protein involved in regulating flagellar and biofilm formation—shared 53.2% genetic similarity with FtcR [ 30 ]. We therefore suspect that FtcR-like regulators could be involved in flagellar biosynthesis and biofilm formation.…”
Section: Introductionmentioning
confidence: 99%